Risk of severe esophageal stricture among childhood cancer survivors – A population-based case-cohort study within the Adult Life after Childhood Cancer in Scandinavia (ALiCCS) - Hansen, Helena K.; Asdahl, Peter H.; Christensen, Jane; Pedersen, Camilla; Krøyer, Anja; Pontoppidan, Celina S.; Holmqvist, Anna S.; Hjorth, Lars; Wiebe, Thomas; Gudmundsdottir, Thorgerdur; de fine Licht, Sofie; Lassen-Ramshad, Yasmin; et al. (EJC paediatric oncology, 2024)
Due to limited data on treatment-related risk factors associated with esophageal stricture in childhood cancer survivors, this study aimed to assess such factors in long-term survivors. A case-cohort study was conducted involving 36 cases of five-year childhood cancer survivors with esophageal stricture and a sub-cohort of 540 survivors diagnosed with cancer in 1970–2007 as identified within the Nordic ‘Adult Life after Childhood Cancer in Scandinavia’ program. Individualized treatment details were retrieved from medical records. Radiation doses to each body region and average dose to the esophagus were reconstructed for patients that received radiotherapy. We used a modified Cox proportional hazard model to evaluate associations between esophageal stricture and risk factors by calculating incidence rate ratio (IRR), with 95 % confidence intervals (CIs). An increased rate of esophageal stricture was found in survivors who received total body irradiation (IRR=13.7, 95 %CI 4.6–41.1), chest- and neck-directed radiotherapy (IRR=23.5, 95 %CI 8.5−64.7) and doses of ≥12 Gy to the esophagus (IRR=26.8, 95 % CI=9.0–80.3) compared to non-irradiated survivors. Treatment with chemotherapy was also associated with esophageal stricture (IRR=8.4, 95 % CI=2.9–24.4). Notably, leukemia survivors faced an elevated rate (IRR=3.8, 95 % CI 1.8–8.1) compared with survivors of CNS and other solid tumors. Our findings indicate an increased risk of esophageal stricture among childhood cancer survivors, with both neck- and chest-directed radiotherapy and chemotherapy as important risk factors. •Esophageal stricture is a rare, serious late effect in childhood cancer survivors.•Chest- and neck-directed radiotherapy increased the risk for esophageal stricture.•A high risk for esophageal stricture was seen for doses ≥12 Gy to the esophagus.•Chemotherapy also increased the risk for esophageal stricture.•Leukemia survivors were at increased risk for esophageal stricture.